2010
DOI: 10.1254/jphs.10r06cr
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin EP Receptors Involved in Modulating Gastrointestinal Mucosal Integrity

Abstract: Abstract. Endogenous prostaglandins (PGs) play an important role in modulating the mucosal integrity and various functions of the gastrointestinal tract, and E type PGs are most effective in these actions. PGE 2 protected against acid-reflux esophagitis and prevented the development of gastric damage induced by ethanol or indomethacin, the effects mimicked by EP1 agonists and attenuated by an EP1 antagonist. Adaptive cytoprotection induced by mild irritants was also attenuated by the EP1 antagonist. On the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 92 publications
2
51
2
Order By: Relevance
“…Mucin secretion. PGE 2 increases gastric mucin secretion and suppression of motor action, and these activities are quite effective in the prevention of gastric mucosal injury (Takeuchi et al, 2010a). It has been reported that EP4 activation promotes mucin secretion from gastric epithelial cells .…”
Section: Other Immune Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mucin secretion. PGE 2 increases gastric mucin secretion and suppression of motor action, and these activities are quite effective in the prevention of gastric mucosal injury (Takeuchi et al, 2010a). It has been reported that EP4 activation promotes mucin secretion from gastric epithelial cells .…”
Section: Other Immune Cellsmentioning
confidence: 99%
“…NSAIDs have been widely used to achieve analgesic and anti-inflammatory effects, but a major limitation to their use is their potential to cause damage to the gastrointestinal mucosa (Levi et al, 1990;Tanaka et al, 2002). The healingimpairing effect of the NSAIDs is due to their inhibition of COX, especially COX-2 Takeuchi et al, 2010a). EP4 activation has been found to attenuate indomethacin-induced intestinal ulcers in rats (Kunikata et al, 2002;Hatazawa et al, 2006;Takeuchi et al, 2010b).…”
Section: Other Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upper gastrointestinal (GI) damage is a major adverse effect of NSAID use (16), and, moreover, recent evidence suggests that NSAIDs are responsible for mucosal injury, not only in the upper, but also the lower GI tract (10,16). Prostaglandin synthesis is considered to play a pivotal role in the mechanism of NSAID-induced GI damage (21); however, its pathophysiology still remains to be elucidated.…”
mentioning
confidence: 99%
“…The protective effect of PG primarily results from an increase in the secretion of HCO 3 -and mucus, which is realized through PG E 1 and PG E 4 receptors [14]. PG receptors on chief cells of the gastric glands probably play a role in the activation of pepsinogen secretion [9].…”
Section: Resultsmentioning
confidence: 99%